Initial Reports of the Deep Sea Drilling Project 1982
DOI: 10.2973/dsdp.proc.64.116.1982
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Interstitial Waters and Sediments, Leg 64, Gulf of California

Abstract: Studies of interstitial waters obtained from DSDP Leg 64 drill sites in the Gulf of California have revealed information both on early diagenetic processes in the sediments resulting from the breakdown of organic matter and on hydrothermal interactions between sediments and hot doleritic sill intrusions into the sediments.In all the sites drilled sulfate reduction occurred as a result of rapid sediment accumulation rates and of relatively high organic carbon contents; in most sites methane production occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 30 publications
(45 reference statements)
9
60
1
3
Order By: Relevance
“…Slightly larger intervals (50 m) were required in a few places because of concern about sampling major stratigraphic boundaries. Shipboard processing of samples and analytical techniques for the various ions are reported elsewhere (Gieskes, 1973(Gieskes, , 1974Gieskes et al, 1982). All squeezing of samples on board was performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Slightly larger intervals (50 m) were required in a few places because of concern about sampling major stratigraphic boundaries. Shipboard processing of samples and analytical techniques for the various ions are reported elsewhere (Gieskes, 1973(Gieskes, , 1974Gieskes et al, 1982). All squeezing of samples on board was performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the δ 13 C cc values of some rift lake volcanics in the Afar Rift (− 7 to − 1‰) are explained as a mixture of meteoric water (~− 15‰) and seawater, with a possible contribution of magmatic CO 2 (~− 5‰) (Fouillac et al 1989), whereas hydrothermal calcite chimneys in Lake Abhé in the Afar Rift have δ 13 C cc values (~2 to 4‰) consistent with that of the alkaline lake water (0.6‰) equilibrated with atmospheric CO 2 (~− 7‰) (Dekov et al 2014). In contrast, all sediment-related settings, such as modern sedimented ridge-derived oceanic crusts and modern/Archean oceanic rift basin basalts, bare relatively low δ 13 C cc values (<− 15‰) as well as the values near the δ 13 C of CO 2 (δ 13 C CO2 ) in seawater which would represent a significant input of CO 2 derived from the decomposition of organic matter (Gieskes et al 1982;Coggon et al 2004;Shibuya et al 2013a). In this regard, the relatively low δ 13 C cc values down to −31.9‰ in the Ongeluk Formation is consistent with its geological setting (a sedimented rifting basin) where decomposition of organic matter in sedimentary rocks (e.g., underlying Makganyene Formation) could occur during the hydrothermal circulation.…”
Section: Variation Of Calcite δmentioning
confidence: 99%
“…In contrast, Jurassic and Cretaceous crusts with penetration depths of > 200 m (Holes 801C, 417A, 417D, and 418A) have higher CO 2 contents, up to 4.2 wt.%, than the younger crusts. It was previously suggested that the enhanced CO 2 uptake by the crust in the Cretaceous period can be explained only (Gillis and Coogan 2011), sedimented ridge-derived MOR crusts (Coggon et al 2004), rift-zone seafloor basalts (Gieskes et al 1982), rift lake basement volcanics (Fouillac et al 1989), and hydrothermal chimney (Dekov et al 2014) from Afar Rift, Archean MOR basalts (Nakamura and Kato 2004;Shibuya et al 2012), and rift-zone seafloor basalts (Shibuya et al 2013a) are also shown by higher seawater temperatures (Brady and Gíslason 1997;Gillis and Coogan 2011). In this case, the high temperature of seawater was likely maintained by the strong greenhouse effect induced by high atmospheric pCO 2 in this era (Berner and Kothavala 2001), as suggested by other geologic records (e.g., paleosols; Ekart et al 1999).…”
Section: Secular Change Of Carbonate Content In the Altered Subseaflomentioning
confidence: 99%
“…Either (1) dilution of GRIND samples to a final sample chlorinity that is below about 250 mmol/kg results in reactions that remove about 75% of the dissolved Li from the sample, or (2) concentrations of Li in samples retrieved below the first sill in Site 857 (471 mbsf) and below the start of lithologic Unit V (mafic extrusive rock) in Holes 858F and 858G (267 mbsf) are generally lower than concentrations in the cooler overlying sediment. Because the Li data are unlike the Na, K, and Rb data and because concentrations of Li generally increase downhole in sediments with intruded sills (Gieskes et al, 1982), we suggest that dilution of pore waters during the GRIND technique greatly impacts the concentration of dissolved Li. This implies the GRIND data for Li are suspect.…”
Section: Minor and Trace Ionsmentioning
confidence: 81%